CLINICAL STUDY OF OPTIMIZED APPROACHES TO LOCAL PREVENTION OF DENTAL CARIES IN PATIENTS WITH TYPE 1 DIABETES MELLITUS - O.A. Udod; A.S. Kulish (Ukrainian Medical Stomatological Academy, 2019)
The prevalence of dental caries is high in people with type 1 diabetes mellitus and it is about 81.1-100%, however 57.1% are diagnosed with multiple dental caries. The effectiveness of caries prevention is only 48.3%. In the prevention of dental caries has significant role to exogenous methods of prevention with fluorides, but fluoride compounds adversely affect the condition of patients with diabetes mellitus. It's advisable to use in patients with caries preventive measures containing nanohydroxyapatite and xylitol. The purpose is to conduct a research of optimized approach to local prevention of dental caries in patients with type 1 diabetes mellitus by the fluoride-free agents, taking into account the degree of risk of dental caries in patients and the state of diabetes compensation. Materials and methods. The review of  95 patients with type 1 diabetes mellitus in the state of compensation, subcompensation and decompensation was from 18 to 35 years and disease duration was from 1 to 24 years. The main group included 50 people, the comparison group was 45 people. The index of caries intensity DMF, structure functional indices of enamel acid resistance (TER) were determined in patients. Also the increase in the intensity of dental caries after 6 and 12 months, reducing the increase in caries after 12 months were defined.The patients of the main group, according to individualized approaches, taking into account the degree of risk of dental caries and the state of compensation of diabetes mellitus were subjected to local caries preventive measures, which included the use of fluoride-free products containing nanohydroxyapatite and xylitol, and means of enzymes lactoperoxidase system, patients of the comparison group - traditional local fluoroprophylaxis. Results and discussion. In patients of the main group after 6 months of caries-preventive measures of structure functional indices of enamel acid resistance was 3.52±0.19 points, 12 months - 3.14±0.16 points, the index improved to 1.7 times (p<0,05), compared to baseline (5.26±0,27 points). In the comparison group of patients, after 6 months, enamel acid resistance was 4.09±0.21 points, after 12 months - 3.86±0.18 points, which is only 1.3 times better (p<0.05) than the baseline index (5.02±0.25 points). Before the start of caries preventive measures, the caries intensity index DMF in patients of the main group was 13.7±0.84, after 6 months it increased to 13.8±0.86, the increase in the intensity of caries was 0.1. In the patients of the comparison group, the corresponding indexes of DMF were 12.3±0.85 and 12.6±0.91, increase the intensity of caries was 0.3 and was higher by 3 times. After 12 months, patients in the main group DMF index slightly increased to 14.0±0.87, increase the intensity of caries was 0.3. In the comparison group DMF index value was 13.1±0.93, increase the intensity was significantly higher (2.7 times) and it was 0.8. Reduction of increase the intensity of dental caries was 62.5%. Conclusion. Topical application in patients with type 1 diabetes mellitus of caries prophylactic agents containing nanohydroxyapatite and xylitol, as well as agents with enzymes of the lactoperoxidase system for 12 months on individualized approaches taking into account the degree of risk of dental caries and the state compensation of diabetes mellitus promoted caries resistance of enamel 1.7 times, reducing the intensity of caries by 2.7 times, allowed to reduction the dental caries growth by 62.5%.